University graduates' transition into the workplace: How they learn to use English for work and cope with language-related challenges. (August 2021) - Chan, Clarice S.C.
Abstract: Despite the large number of university graduates who use English as a second language at work, little is known about the language socialization process they undergo as new employees. The present paper addresses this gap by investigating how three recent Hong Kong graduates learned to use English for work and how they overcame their communication challenges. The three informants were all English majors who had not received training to work in any particular field and who had to learn the discursive and professional practices of a field new to them. It was found that they encountered difficulties with various non-specialist genres, and that the difficulties stemmed mainly from a lack of knowledge of their field and/or an inadequate level of English proficiency. It was also found that the graduates used various strategies to learn workplace communication and solve language-related problems, but that their vulnerable sense of professional identity sometimes prevented them from using some possibly more effective ways of overcoming communication challenges, such as seeking help from more experienced members of their community of practice. The paper has implications for language educators who want to help university students be better prepared for workplace communication in English after graduation.